Transcranial Direct Current Stimulation Altered Voluntary Cooperative Norms Compliance Under Equal Decision-Making Power - Li, Jianbiao; Liu, Xiaoli; Yin, Xile; Li, Shuaiqi; Wang, Guangrong; Niu, Xiaofei; Zhu, Chengkang (Frontiers in Human Neuroscience, 2018)
Social norms play an essential role in human interactions and the development of the evolution of human history. Extensive studies corroborate that compliance with social norms typically requires a punishment threat as almost always specific individuals have self-interests that tempt them to violate the norm. Neural imaging studies demonstrate that lateral orbitofrontal cortex and right dorsolateral prefrontal cortex (rDLPFC) are activated when individuals decide to increase social norm compliance when punishment is possible. Moreover, rDLPFC is affirmed to be involved in social norm compliance with or without external punishment threats in a series of transcranial direct current stimulation (tDCS) research. However, these neuroscience studies are based on the ultimatum game in which the decision-making power between the proposer and the responder is unequal, and no studies support the causal relationship between rDLPFC and voluntary cooperative norms compliance among the equal decision-making power of subjects. Whether modulating the excitability of rDLPFC, which plays a role in norm compliance, alters the extent of compliance with voluntary cooperative norms under equal decision-making power and how norms from different types with asymmetric endowment influence compliance remain unknown. The present study aimed to provide evidence of a direct link between the neural and behavioral results through the application of tDCS over rDLPFC on compliance with voluntary cooperative norms under equal decision-making power. Results verified that activating rDLPFC altered voluntary cooperative norms compliance of all our participants and significant effect over different initial endowments was observed. The role of norm.own and norm.other in compliance was changed in the anodal treatment. Findings validate that enhancing the excitability of the rDLPFC using tDCS leads to high compliance in voluntary cooperation and this effect is specific to equal decision-making power rather than unequal decision-making power.